INOVASI MINUMAN CENDOL DAN JAMU (CENJA) ERA MILENIAL DI KELURAHAN 20 IlIR D II KECAMATAN KEMUNING KOTA PALEMBANG - Syaparman, Syaparman; Austin, Trecy; Ibrahim, Ibrahim (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2022)
Modernization is made to improve the mindset and quality as well as the life motto of traditional people in a region or country. After modernization is carried out, new innovations will arise in all lines of life, one of which is in the food and beverage business. In the millennial era, the food and beverage business is increasingly modern and has the latest innovations. And with the internet, distribution of these innovation products to the public will be much easier, the arrival of the Covid-19 virus has a negative impact on the economic aspects of people in Indonesia, especially in the 20 Ilir D II sub-district, Kemuning District, Palembang City and business actors are required to create new innovations. their products in order to attract the interest of the wider community. In this condition, assistance and dedication from universities is needed to be able to foster and guide SME entrepreneurs to be able to develop their businesses. In the realization of this service, starting from the preparation, implementation and evaluation stages using the family method with the concept of an emotional approach with the local community in diversifying their products. As a result, entrepreneurs who become partners can diversify their products into several variants that can increase sales volume.